Decreased Postural Sway in Women Who Are Visually Impaired: Is it a Learned Protective Mechanism?. (July 2022) - Rashid, Muhammed; Siby, Sherin; P. H., Sandeep; Joy, Anoop; Gopi, Arun; Mathew, Jerin; Raja, Kavitha
Introduction: Comparison of sway parameters of visually impaired participants to that of the sighted population may give insight into the intrinsic risk of falls relative to the surface. Sway is a natural mechanism to adjust the posture and maintain balance. But the sway characteristics on uneven surfaces are ill explored. There is a paucity of evidence on baseline values of sway amplitude in visually impaired women in comparison to sighted women, which underpins the importance of this study.Methods: Eighteen visually impaired young women and an equal number of age-matched sighted peers were recruited by convenience to this prospective observational study. Sway amplitude of the participants were measured using a sway meter on three different surfaces, with eyes opened and closed conditions, using videography and analyzed using Kinovea motion analyzing software. Demographics and participant characteristics were summarized using descriptive statistics. The comparison were performed using independent sample t -test.Results: Visually impaired women demonstrated lower amplitude of sway than sighted young women, irrespective of the surface.Discussion: There was a gradual increase in sway amplitude as the standing surfaces changed from even to sand and pebbles, respectively, for both groups.Implications for Practitioners: Contrary to the existing evidence, the results of this study indicate that visually impaired young individuals may not be not at higher intrinsic risk of falls on various terrains than their sighted peers. The authors hypothesize that the lower sway among visually impaired participants can be attributed to the learned strategy for safety from exposure to real-life pragmatic environments during everyday activities, which enabled them to adopt postural strategies as a safety measure. Hence, this strategy can potentially be used in dynamic situations to decrease the propensity for falls during ambulation in visually impaired individuals.